Post hoc analysis of the results of KOLIBRI comparative observational clinical study in patients with knee and small hand joints osteoarthritis - A. Yu. Feklistov; L. D. Vorobieva; O. G. Alekseeva; A. V. Sukhinina; I. A. Andrianova; I. V. Menshikova; V. N. Sorotskaya; E. G. Zotkin (Современная ревматология, 2022)
Objective: to evaluate the effectiveness of therapy with AMBENE®Bio (AB) in comparison with the comparator drug (bioactive concentrate of small marine fish, BCSMF) in patients with osteoarthritis (OA) of large and small joints in routine clinical practice.Patients and methods. KOLIBRI multicenter, observational, non-randomized, comparative study included 233 patients with OA of the small hand joints (HJ) or knee joints (KJ) from three Russian centers (two in Moscow and one in Tula). Patients with a generalized form of OA were excluded from the analysis. The remaining patients were divided into two groups depending on the localization of OA. The first group included 174 patients with knee OA, 105 of them received AB, and 69 received the reference drug (BCSMF) according to the same regimen. The second group consisted of 21 women with HJ OA: 13 patients were prescribed AB, and 8 — the reference drug.The duration of the study averaged 330±14 days, the total number of visits was 4. The main indicator of effectiveness was the dynamics of pain during movement according to VAS (0—100 mm) 30±7 days after the start of treatment compared with the baseline value. All patients underwent radiography of the HJ and KJ, as well as ultrasound of the involved joints.Results and discussion. Both drugs provided significant clinical improvement in patients with OA, which is consistent with other studies with similar design and long follow-up. These data confirm the symptom-modifying properties of the presented group of combined drugs in the OA treatment. The Russian injectable drug AB in OA was not inferior in effectiveness to the foreign BCSMF. According to the OMERACT-OARSI criteria, 85.2% and 88.9% of patients, respectively, responded to treatment with AB and the reference drug. In both groups, half of the patients managed to stop further use of non-steroidal anti-inflammatory drugs (NSAIDs) on a regular basis.Conclusion. The use of AB was accompanied not only by a decrease in the severity of clinical symptoms of OA, but also by a decrease in the daily requirement for NSAIDs almost by 2 times.